THE EFFECT OF USE VIDEO IN THE MODEL OF QUIDED INQUIRY LEARNING ON TRAVELING WAVES AND SOUND WAVES MATERIALS IN CLASS XI SMA NEGERI 7 SIJUNJUNG - Nikita Suryani; Yurnetti Yurnetti; Amali Putra; Desnita Desnita (Universitas Negeri Padang, 2021)
The many technological discoveries of the 21st century require the world of education to adapt quickly. Based on curriculum 2013’s competence standards. Then it requires reinforcement of a scientific approach to add in learning. But in the fact remains that the learning model demands the 2013 curriculum and the 21st-century technology-based learning medium is not fully finish. Researchers have attempted to study using video as a learning medium in guided inquiry learning to look at the impact on learning participants. The kind of research being done is a quasi-experiment research design with the randomized research group one design. The population in this research are all public high school seniors registered in 2020/2021. Samples from this research are XI MIPA 1 as experiment class and XI MIPA 2 as control class. The research instrument consists of posttest and performance assessment sheets. The data on this research is analyzed using a two average descriptive analysis and testing similarities ate definite point 0,05 for the competence of students made up of knowledge and skill. Studies have concluded that there is an influence that means use the video in guided inquiry learning to traveling wave and sound waves in XI SMA Negeri 7 Sijunjung. It is supported by has data analysis on each knowledge and skill competence with two averages found th> ttable. At the competence knowledge, 4,824>2,002 and at skill competence 4,098>2,002 who are in the Ho rejection area means there are differenct results for the competence of knowledge and student’ skills.